A dipeptidyl peptidase IV inhibitory peptide relieves palmitic acid-induced endoplasmic reticulum stress in HepG2 cells independent of inhibiting dipeptidyl peptidase IV activity. Issue 21 (5th October 2021) - Jin, Ritian; Ren, Haowei; Liao, Minhe; Shang, Jiaqi; Wang, Dangfeng; Li, Meng; Liu, Ning
Abstract : The peptide VLATSGPG (VLA) is known to inhibit dipeptidyl peptidase IV (DPP-IV), although its mechanism in relieving endoplasmic reticulum (ER) stress is unclear. Abstract : The peptide VLATSGPG (VLA) is known to inhibit dipeptidyl peptidase IV (DPP-IV), although its mechanism in relieving endoplasmic reticulum (ER) stress is unclear. In this study, we found that treating HepG2 cells with 1.0 mM VLA reduced DPP-IV activity by 73.7 ± 4.8% without changing the DPP-IV mRNA expression level. In addition, 1.0 and 0.5 mM VLA alleviated palmitic acid (PA)-induced cell death and intracellular calcium imbalances. The levels of apoptosis-related proteins (caspase-3, caspase-9, and CHOP) were reduced by VLA treatment, which was presumed to be related to ER stress. Further studies confirmed that VLA alleviated PA-induced morphological damage to the ER and reduced the levels of the ER stress marker proteins (BIP, p-PERK, and p-IRE1α). VLA alleviated PA-induced ER stress in HepG2 cells independent of DPP-IV enzymatic activity inhibition. These findings have implications for developing novel treatment approaches for liver diseases caused by ER stress.